A Multi-Faceted Approach to Urban Congestion in Developing Nations: Theory, Practice, and the Kathmandu Experience - Luitel, Sanjay; Subedi, Abhishek Kumar; Nepal, Saujanya; Tiwari, Hemant (Journal of Advanced College of Engineering and Management, 2025)
Urban traffic congestion poses a critical barrier to sustainable development in rapidly urbanizing regions, particularly in the Global South. This review examines the theoretical foundations of congestion, outlining core metrics and classical models, and assesses a range of mitigation strategies implemented in developing countries. Drawing on international case studies including Delhi, Dhaka, Lagos, and Nairobi, the article analyzes the effectiveness of infrastructure expansion, traffic management innovations, and public transport reforms. Kathmandu Valley serves as a focal case, exemplifying how rampant motorization, inadequate infrastructure, and fragmented governance contribute to chronic congestion. Despite some efforts in signal optimization and public transport modernization, systemic challenges persist. Comparative insights reveal that enduring congestion mitigation requires a multimodal, data-driven approach that encompasses intelligent traffic systems, public transit investment, and institutional reform. The paper concludes with tailored policy recommendations for Kathmandu, emphasizing the need for coherent, scalable, and locally responsive mobility strategies.